Fostering disabled children in Greece: Insights into foster mothers’ experiences, motivations, challenges and satisfaction - Xanthaki, Margarita; Anagnostaki, Lida (Adoption & fostering, 2025)
International research on the motivations, challenges and levels of satisfaction of foster parents of disabled children is limited and has only been carried out in specific sociocultural and legal contexts. Studying fostering in diverse cultural settings is important not only out of scientific interest, but also because contextual differences may influence the fostering experience. The present qualitative study explored the experiences of Greek foster mothers of disabled children – to our knowledge, the first study of its kind in Greece. Data were collected through semi-structured interviews with a sample of eight foster mothers of disabled children. Thematic analysis revealed that the motivations of foster mothers were related to the child’s disability, the emotional relationship developed with the child and a sense of charity. Several challenges were identified, such as difficulties in collaborating with institutional staff, managing multiple roles, maintaining social and personal relationships and handling the disruptive behaviour of the foster child. Participants also expressed concern about the future of the foster children without their support, while most expressed satisfaction with fostering. Finally, an unexpected theme emerged during the interviews concerning the neglect and abuse of disabled children in Greek institutions. Plain language summary Studying fostering in diverse cultural settings is crucial not only for scientific purposes but also because variations in cultural and legal contexts can impact the fostering experience. However, international research on the motivations, challenges and levels of satisfaction of foster parents of disabled children is limited and has only been carried out in specific cultural contexts, namely the US and Canada. The present study explored the experiences of Greek foster mothers of disabled children, which, to our knowledge, is the first study in Greece on this topic. Data were collected through semi-structured interviews for a sample of eight foster mothers of disabled children. The motivations of foster mothers were related to the child’s disability, the emotional relationship developed with the child and a sense of charity. Several challenges were identified, such as difficulties in collaborating with institutional staff, managing multiple roles, maintaining social and personal relationships and handling the disruptive behaviour of the foster child. Participants expressed concern about the future of the foster children without their support, while most of them expressed satisfaction with fostering. Finally, an unexpected theme emerged during the interviews concerning the neglect and abuse of disabled children in Greek institutions.